Efek Faktor Individu, Manajemen dan Pendukung Terhadap Penundaan Operasi Elektif - Sriwardani, Endang; Wijaya, Dodi; A’la, Muhamad Zulfatul (FORIKES, 2025)
Delays in elective surgery are considered a fundamental problem in healthcare because they cause significant disruptions to patient flow, further exacerbating already limited operational capacity, and consequently reducing hospital performance and patient satisfaction. The purpose of this study was to determine the reasons for surgical delays across hospitals and countries. The method used in this study was a literature review. The search terms used were